Dynamics of Public Infrastructure, Industrial Productivity and Profitability - Shah, Anwar (The Review of Economics and Statistics, 1992)
A restricted equilibrium framework is utilized to estimate the contribution of public investment in infrastructure to private sector profitability. A restricted cost function in translog form which treats labor and materials as variable inputs and private capital and public sector capital stock in transportation, communications and electricity as quasi-fixed inputs is specified. A system of non-linear equations comprising variable cost function and derived input demand equations is estimated using data from 1970 to 1987 for twenty-six Mexican three-digit manufacturing industries. The divergence of private and public capital stocks from their static equilibrium levels is estimated. The net rate of return to fixed factors is also calculated. Estimates of allocative efficiency are derived. The study further provides estimates of short-run and long-run scale economies, output elasticity of factors, measures of productivity growth and technical change. Economic significance and policy implications of the findings are also presented. Copyright 1992 by MIT Press.